Forest Transformation Following European Settlement in the Saguenay-Lac-St-Jean Valley in Eastern Québec, Canada - Dupuis, Sébastien; Danneyrolles, Victor; Laflamme, Jason; Boucher, Yan; Arseneault, Dominique (Frontiers in Ecology and Evolution, 2020)
Human activities have changed forest composition of northeastern North America since European settlement by increasing the importance of pioneer shade-intolerant species, at the expense of shade-tolerant and long-lived species. This study used tree taxa lists from land survey archives (1842-1935) to document the pre-settlement forest composition in a heavily transformed region at the temperate-boreal interface in eastern Québec (Canada). Pre-settlement forests were dominated by a spruce-fir-white birch assemblage. Two additional assemblages were characterized by high relative frequency of the fire-adapted jack pine and poplar, suggesting that fire was an important factor of pre-settlement forest dynamics. Comparison with modern forest inventories (1980-2010) showed that trembling aspen, jack pine and red maple increased to the detriment of spruce, yellow birch, and white and red pines. The spruce-fir-white birch assemblage is now confined to high elevations and steep slopes, while the jack pine assemblage has extended its distribution and strengthen its association with sandy deposits. Surveyors' fire observations revealed a high fire activity during the settlement period (1842-1971) and human ignitions were probably the predominant cause. While settlement fires are a likely explanation for the post-settlement increase of jack pine and trembling aspen, industrial logging and land clearing are important factors that could explain the decline of spruce and pines (red and white). Ecosystem-based forest management should aim to increase spruce prevalence and dominance over disturbance-adapted (shade intolerant, fast-growing) species, and to restore yellow birch, cedar, white and red pines in the plains sector where forest transformation has been the most important.